Co-creating Urban Environments to Engage Citizens in a Low-carbon Future. (2017) - Davis, Aaron; Andrew, Jane
Abstract: As cities try to lower their carbon footprints, the concept of transforming brownfield sites into 'eco-precincts' has gained substantial traction. There is not yet however, an established way of combining technological innovation with social and behaviour change. The design, and operation of an 'eco-precinct' requires the cooperation of a wide variety of disciplines and stakeholders. Without this cooperation, there is often a disparity between the aspirations for these precincts and the final outcomes. Co-creation is increasingly being looked-to to support precinct development in that it facilitates deeper user engagement in the design process. There a number of challenges to applying co-creative models to larger scales of development. One of which is defining the user in greenfield or brownfield development. This complexity is added to by the perceived risk to budgets and timelines due to the uncertainty associated with the feedback loops of the co-creation process, and the complex power dynamics and process challenges between various professional and non-professional actors. This paper suggests that addressing these challenges is critical in facilitating a shift from 'consultation' (both professional and public) being considered as a discrete event (noun), to an ongoing and iterative process (verb) that can facilitate the creation of innovative user centred low-carbon urban environments.